STUDENTS’ PERCEPTION OF THE USE OF THE SCRABBLE GAME AS A LEARNING TECHNIQUE IN LEARNING VOCABULARY - Ridisrawan, Akhmad Muflih; Talib, Ahmad; Abduh, Amirullah (Universitas Negeri Makassar, 2022)
The objectives of this study were to find out the students’ perception of the use of the Scrabble game as a learning technique for learning vocabulary and to find out the problems that the students face when learning vocabulary. A mixed-method design was used in this study. The population of this research was the students of Ponpes DDI Mattoanging Bantaeng in the academic year 2022/2023. Through the purposive sampling technique, 20 students in an English meeting of Ponpes DDI Mattoanging Bantaeng were chosen to be the sample of this research. The instruments of this research were a questionnaire and an interview. The research findings showed that eight students (40%) have a strongly positive perception, seven students (35%) have a positive perception, two students (10%) have a negative perception, and there are three students (15%) have a strongly negative perception. Based on the data, it can be concluded that the students positively perceive the use of the Scrabble game as a learning technique for learning vocabulary. There are three problems that the students face when learning vocabulary. They are students who find it hard in pronouncing, writing vocabulary, and memorizing vocabulary.